As inovações sociais: uma incursão por ideias, tendências e focos de pesquisa - Luiz Paulo Bignetti (Ciências Sociais Unisinos)
This article starts from the paradox that, despite the amplitude of social problems and the increasing preoccupation with market failures that cause inequalities, social innovation studies still do not represent a major proportion of academic research. The existing approaches, methodologies and practices do not yet constitute a consolidated body of knowledge and there is no strong theory to support them. Therefore, the article presents a preliminary discussion of how social innovations are developed and disseminated and offers some contributions to the establishment of theoretical references and frameworks for the studies about innovative social practices. The fundamental argument expounded here is that studies about social innovation are not similar to those about technological innovation. The character of the processes of development and dissemination of social innovations is considered to be unique and therefore should not be treated according to the same theoretical principles applied to technological innovation. It is proposed that studies on social innovations could be conducted according to three main avenues of research: social entrepreneurship, social organizations and social movements. The most important discussions found in the literature are presented.